Response of sedimentation processes in the Minjiang River subaqueous delta to anthropogenic activities in the river basin. (5th January 2020) - Ai-jun, Wang; Xiang, Ye; Zhen-kun, Lin; Liang, Wang; Jing, Lin
Abstract: Sedimentary processes in the subaqueous deltas of small mountainous rivers are very sensitive to environmental variation within the river basin and hydrodynamic conditions near the estuarine environment. Through radiometric dating and sediment grain size analysis of core sediments collected in the subaqueous delta area of the Minjiang River (MJR), we studied the sedimentary processes in this area since the 1950s and revealed their responses to human activities within the MJR basin. The dry density of core sediments in the MJR subaqueous delta varied from 0.81 to 1.32 g/cm 3 . The mean sedimentation rate was 0.61 cm/yr (0.68 g/cm 2 ⋅yr) before 1963, and has increased to 1.04 cm/yr (1.05 g/cm 2 ⋅yr) between 1963 and 1986, and then decreased to 0.46 cm/yr (0.41 g/cm 2 ⋅yr) between 1986 and 2014. The core sediments were composed primarily of silt, and the main sediment type was clayey silt; the mean grain size varied from 5.1 to 22.3 μm, with a mean value of 10.3 μm. With increasing anthropogenic activity within the MJR catchment, the land use pattern changed markedly. Soil erosion intensified, and the sediment flux discharged by the MJR to the sea clearly increased; consequently, the sedimentation rate in the subaqueous delta also increased. However, owing to dam construction, large quantities of sediment were trapped within reservoirs, decreasing the sediment flux discharged by the MJR to the sea, affecting the sedimentation rate in the subaqueous delta and also changing the sediment frequency curve from a bimodal pattern to a single-peak pattern. Highlights: Soil erosion induced by land use change accelerates the sedimentation rate in subaqueous delta. Dam construction decreases the sedimentation rate in subaqueous delta. Anthropogenic activities alter the grain-size composition.